2021
DOI: 10.3390/microorganisms9061165
|View full text |Cite
|
Sign up to set email alerts
|

Studying Microbial Communities through Co-Occurrence Network Analyses during Processes of Waste Treatment and in Organically Amended Soils: A Review

Abstract: Organic wastes have the potential to be used as soil organic amendments after undergoing a process of stabilization such as composting or as a resource of renewable energy by anaerobic digestion (AD). Both composting and AD are well-known, eco-friendly approaches to eliminate and recycle massive amounts of wastes. Likewise, the application of compost amendments and digestate (the by-product resulting from AD) has been proposed as an effective way of improving soil fertility. The study of microbial communities … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(10 citation statements)
references
References 112 publications
0
10
0
Order By: Relevance
“…In addition, ISCM could significantly affect microbial network density and change with the crop growth stage ( Figure 2 ), which was closely related to the agronomic management practices in each period. The microorganism network density of T3 was the highest among the four treatments (except for the R6), which may be related to the fact that heavy fertilization accelerated the growth of soil microorganisms ( Siles et al, 2021 ), but too many microbes may lead to increased competition and increase more negative interactions between species ( Ratzke et al, 2020 ). However, Giovannoni et al (2014) showed that microorganisms tend to coexist in large numbers in low nutrient environments.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, ISCM could significantly affect microbial network density and change with the crop growth stage ( Figure 2 ), which was closely related to the agronomic management practices in each period. The microorganism network density of T3 was the highest among the four treatments (except for the R6), which may be related to the fact that heavy fertilization accelerated the growth of soil microorganisms ( Siles et al, 2021 ), but too many microbes may lead to increased competition and increase more negative interactions between species ( Ratzke et al, 2020 ). However, Giovannoni et al (2014) showed that microorganisms tend to coexist in large numbers in low nutrient environments.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the high number of correlations could be due to a greater number of niches in Org_C, which could allow a greater number of different habitats. However, this is not entirely in accordance with the increased network complexity of Org_C, which suggests that module members are less affected by environmental perturbations [56,57]. Total nitrogen correlated positively with a module from Org_C (OC7), and this module was composed of Nitrospirae, where members of Nitrospira show the capability to perform complete nitrification [58,59], or Actinobacteria, where genera like Streptomyces have been linked to some nitrogen-fixation genes [60,61].…”
Section: Discussionmentioning
confidence: 98%
“…Modularity is another useful index to investigate the resistance of communities to disturbance ( Zhou et al, 2011 ), which are clusters of densely interconnected nodes ( Siles et al, 2021 ), and has been used to successfully predict the stability of networks of microbiomes ( Herren and McMahon, 2017 ; De Vries et al, 2018 ). Krause et al (2003) found that higher modularity was beneficial for increasing the stability of interaction networks and helping microbial communities resist environmental changes.…”
Section: Discussionmentioning
confidence: 99%